A place to live : the story of Triangle Square - Coal, Carolyn; Childs, Cynthia; Bittersweet Productions (Film production company); NoCo Media Group; Leomark Studios ([Los Angeles, California] : Bittersweet Productions : NoCo Media Group, 2008)
Follow the journey of seven gay and lesbian seniors as they attempt to secure an apartment in Triangle Square, the nation's first affordable housing facility for LGBTQ seniors in Los Angeles. It's both a touching portrait of the individuals who survived persecution, discrimination, and homophobia as well as the triumph of the opening of a historic building.
Originally released as a motion picture in 2008.
Featuring: Art Aguirre, Karen Dickinson, Bill LaVallee, Don Norman, Phil Radtke, Margo Strik, Nancy Valverde.
Editor, Susan Munro ; music, Marika Tjelios.
In English; closed captioned available.
Winner of the Award of Best Documentary, at the L.A. Outfest 2008.
Winner of the Award of Best Documentary Feature, at the Long Beach QFilm Festival 2009.
Keywords: Triangle Square (Hollywood, Calif.); Older gays -- Housing -- California -- Los Angeles; Older lesbians -- Housing -- California -- Los Angeles; Older gay men -- Housing -- California -- Los Angeles; Low-income housing -- California -- Los Angeles; Nonfiction films; Documentary films; Internet videos; Streaming video